Colaboradores: Collaborators - Geraldello, Camilla Silva (Faculdade de Filosofia e Ciências, 2018)
Alexandre César Cunha Leite Ariel González Levaggi Arthur Mastroiani Maximo de Lucena Augusto César Dall’Agnol Daniel Morales Ruvalcaba Fábio Nobre Julieta Zelicovich Luís Antonio Paulino Luis L. Schenoni  Marcos Cordeiro Pires   Pedro Vinícius Pereira Brites Thaís Caroline Lacerda Mattos